PENGARUH KOMUNITAS MEREK TERHADAP LOYALITAS MEREK, MELALUI NILAI PELANGGAN SEBAGAI VARIABEL INTERVENING PADA YAMAHA VIXION CLUB INDONESIA CHAPTER SEMARANG - Maharani, Intan Nur; Farida, Naili; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2012)
The purpose of this study is to determine the effect of brand community brand loyalty through customer value on the Yamaha Vixion Club Indonesia Chapter Semarang. Which is in this study were divided into three communities brand awareness variables together, rituals and traditions, and moral responsibility. This type of research is explanatory, with the technique of collecting data through questionnaires. The sampling technique used purposive sampling technique, the sample of 40 peoples who are members of the Yamaha Vixion Club Indonesia Chapter Semarang. The method of analysis used in this study is Part Analiyst. Based on the calculations show that there is a variable effect of collective consciousness, rituals and traditions, moral responsibility, and customer value significant positive effect on brand loyalty in the amount of 66.7%.Based on the analysis of pathways directly influences have a greater value than the indirect effect, it shows a member of the community with brand customer will immediately have a sense of loyalty to the brand without having to feel the value or benefits as a member of the community.